Pengaruh Metode Diskusi Dalam Meningkatkan Motivasi Belajar Seni Tari Pada Kelas VIII 1 Di UPT SMP N 2 X Koto - Sri Muryenti; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2020)
This article aims to describe the effect of discussionmethod in improvingdancearts learning motivationat class VIII I in UPT SMP N 2 X Koto. This type of research was a qualitative study with using descriptive method. The main instrument in this study was the researcher. It was assisted by supporting instruments such as stationery and camera. Tehniques ofdata collection in this research were done by doing observation, interview and literature study. The steps in analyzing data were collecting, selecting, presenting and testing data, then thedata were interpreted and concluded. The results show that the discussion method can effect students' motivation in learning cultural arts (dance). The improvement of student motivation can be seen from the number of students who are active in the learning process. Indicators that can be referenced to state the effect of the discussion method on students' motivation in learning dance in SMP N 2 X Koto is that there is a change in energy from being soft or less responsive and not really improving to being reactive and there has been seriousness in learning.